2015
DOI: 10.7567/apex.8.043004
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical evaluation of the temperature dependence of magnetic anisotropy constants of Nd2Fe14B: Effects of exchange field and crystal field strength

Abstract: To identify the possible mechanism of coercivity (H c ) degradation of Nd-Fe-B sintered magnets, we study the roles of the exchange field acting on the 4f electrons in Nd ions and theoretically investigate how the variation of the exchange field affects the values of the magnetic anisotropy constants K 1 and K 2 . We find that, with decreasing exchange field strength, both values decrease as a result of the lower asphericity of the 4f electron cloud, indicating that the local anisotropy constants might become … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 20 publications
7
22
0
Order By: Relevance
“…We can see that below 150 K, K eff 1 is negative and both K eff 2 and K eff 3 play a critical role, agreeing Fig. 3(c) agrees reasonably with the previous experimental measurement [42,43,49] and theoretical calculations [24,50].…”
Section: B Effective Magnetic Anisotropysupporting
confidence: 91%
“…We can see that below 150 K, K eff 1 is negative and both K eff 2 and K eff 3 play a critical role, agreeing Fig. 3(c) agrees reasonably with the previous experimental measurement [42,43,49] and theoretical calculations [24,50].…”
Section: B Effective Magnetic Anisotropysupporting
confidence: 91%
“…In the lowtemperature range below the spin-reorientation transition (SRT) temperature (T ∼ 130 K [45]), these compounds exhibit complex behavior as shown by the lines for T = 0, 100, and 135 K. Above the SRT temperature, we can observe that ∆Θ < 0 because M Nd (θ, φ; T ) tends to naively orient along the +z-axis, and that |∆Θ| monotonically decreases with increasing temperature. In Nd 2 Fe 14 B magnets, |∆Θ| has an extremely low value over the entire temperature range, and thus we conclude that the NCE is negligibly small as assumed in our previous studies [24][25][26].…”
Section: Introductionsupporting
confidence: 76%
“…In our previous studies on the MA of Nd 2 Fe 14 B magnets [24][25][26], the total magnetization was assumed to be collinear to the Fe magnetization. However, this assumption raises a serious error in evaluations for the MA of the R 2 Fe 14 B magnet, the R magnetization of which is highly non-collinear to its Fe magnetization.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we emphasize that the common parameters in the two comparisons are used in µ Nd (T ), and particularly that the value of H Nd = 350 K is reasonable because the strength of the EXF strongly influences the plateau of the MACs appearing in the low-temperature range. 9 In addition, we must consider the non-collinearity between the R and Fe moments. Although the MACs of R =Nd obey the present power law well, this is not the case for magnets with a high non-collinearity.…”
Section: Temperature Dependence Of Macs In R 2 Fe 14 B Magnetsmentioning
confidence: 99%
“…For example, Yamada et al showed through their systematic analysis of the magnetization process for the R 2 Fe 14 B series that parameters representing crystalline electric fields (CEFs) and effective exchange fields (EXFs) at R sites do not depend significantly on R. 8 Furthermore, we have previously confirmed that an effective Hamiltonian using the parameters suitably describes the experimental temperature dependence of the magnetocrystalline anisotropy constants (MACs) of Nd 2 Fe 14 B magnets. 9,10 However, there remains a gap between our microscopic picture and the macroscopic aspects of MA since previous theoretical studies on the temperature dependence of MA for R 2 Fe 14 B magnets are based on complete diagonalization of the Hamiltonian 9,10 or numerical methods such as the Monte Carlo method. 4,11,12 An effective means of bridging this gap is to develop a power-law theory 5,6,[13][14][15][16][17][18] to establish the relationship between MACs and magnetization.…”
Section: Introductionmentioning
confidence: 99%